PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 05 SAMSAM KECAMATAN KANDIS KABUPATEN SIAK - Sartika, Dewi; Antosa, Zariul; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems on the background of this research were the low of learning achievement in natural science subject. During the learning process the teachers only use the speech method. The teacher just opened the lesson and directly presented the subject. Then they gaveassignments as training and little motivation for the students. It could be seen from the problems that arisedsuch as the students tend to be passive, and just listened while the teacher explained the lesson. The Students could not solve the problems that they faced in their life. And the Students did not do the assignment that gave by teachers. One of solutions that could improve their learning achievement at grade IV in natural science subjectwas the Implementation of Learning Model studentsbased on problems in order to be applied in their life. The subjects of this research was the fourth grade students of SDN 05 Samsam District of Kandis Regency of Siak, it was 35 students consistied of 20 male students and 15 female students. This research was a classroom action research, it done in two cycles, each cycle conducted twice and once daily test. The purpose of this research was to improve science learning achievement in fourth grade of SDN 05 Samsam District of Kandis Regency of Siak. The main subject of this research was the source thermal energy. The results showed that the application of learning model based on the problem to improve learning achievement of IPA before being applied which Problem Based on Learning Model was 64.71. After being applied Learning Model Based on Problem, In daily test of cycle I the average value of student learning achievement was 70.86, it was an increase. The meeting was continued to the second cycle, and the second cycle of daily test average value of student learning achievement was 82.57. Based on the explanation above could be concluded that the implamentation of learning models based on problems could improve student learning achievement of fourth grade of SDN 05 Samsam District of Kandis Regency of Siak.Keywords : Learning model Based on Problem, to improve student learning achievement of IPA